2000
DOI: 10.1126/science.287.5460.2017
|View full text |Cite
|
Sign up to set email alerts
|

Facile Detection of Mitochondrial DNA Mutations in Tumors and Bodily Fluids

Abstract: Examination of human bladder, head and neck, and lung primary tumors revealed a high frequency of mitochondrial DNA (mtDNA) mutations. The majority of these somatic mutations were homoplasmic in nature, indicating that the mutant mtDNA became dominant in tumor cells. The mutated mtDNA was readily detectable in paired bodily fluids from each type of cancer and was 19 to 220 times as abundant as mutated nuclear p53 DNA. By virtue of their clonal nature and high copy number, mitochondrial mutations may provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
596
5
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 761 publications
(625 citation statements)
references
References 15 publications
21
596
5
3
Order By: Relevance
“…In the present study, which is the largest series of HNSCC analysed for mtDNA mutations in the literature, we report a 21% frequency of D-Loop somatic mutations. This frequency is similar to that obtained by Fliss et al (2000) who performed a sequence analysis of 80% of the mitochondrial genome and found a D-Loop mutation in three of 13 (23%) HNSCC patients. However, other studies on small series of patients reported more frequent D-Loop mutations, ranging from 37 to 61% Ha et al, 2002;Poetsch et al, 2004) of the cases.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, which is the largest series of HNSCC analysed for mtDNA mutations in the literature, we report a 21% frequency of D-Loop somatic mutations. This frequency is similar to that obtained by Fliss et al (2000) who performed a sequence analysis of 80% of the mitochondrial genome and found a D-Loop mutation in three of 13 (23%) HNSCC patients. However, other studies on small series of patients reported more frequent D-Loop mutations, ranging from 37 to 61% Ha et al, 2002;Poetsch et al, 2004) of the cases.…”
Section: Discussionsupporting
confidence: 89%
“…We showed that tumours located in the hypopharynx (24.8% of all tumours) were significantly more mutated than tumours in other sites. Proportion of hypopharynx tumours is not known in the other studies (Fliss et al, 2000;Sanchez-Cespedes et al, 2001;Ha et al, 2002;Poetsch et al, 2004). So, we can speculate that a higher proportion of tumours located in the hypopharynx would be associated with a higher frequency of mtDNA mutation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Recently, somatic mutations in the mitochondrial DNA (mtDNA) have been identified in various human cancers such as colon cancer, gastric cancer and HCC (Polyak et al, 1998;Fliss et al, 2000;Nishikawa et al, 2001;Sanchez-Cespedes et al, 2001). Human mtDNA is a 16.5-kb circular double-stranded DNA molecule, which contains genes coding for 13 polypeptides involved in respiration and oxidative phosphorylation, two rRNAs and a set of 22 tRNAs that are essential for protein synthesis in mitochondria (Anderson et al, 1981).…”
mentioning
confidence: 99%